Fifteenth International Symposium on Quality Electronic Design 2014
DOI: 10.1109/isqed.2014.6783395
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of process variation induced SRAM electromigration degradation

Abstract: Electromigration (EM) greatly affects the long term reliability of VLSI chips. Not only power/ground (P/G) lines, but also bit-lines of SRAM arrays may be damaged by EM. In this work, we demonstrate that the EM reliability of an SRAM array can be dramatically worsened by process variation due to a significant increase of sub-threshold leakage current on the bit-line. We statistically model the effects of process variation and offer a procedure for preventing EM failure by modifying the width of bit-lines and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We evaluated four different memory bit-cells with each being designed at the same condition of 10 ns switching time; 2 ns sensing time; 15% write margin; defined as (I W -I C )/I C ; and >40% read-disturb margin, defined as (I C -I R )/I C , in an array comprising 256 rows and 512 columns [29][30][31]. See Table 2 for simulation results.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…We evaluated four different memory bit-cells with each being designed at the same condition of 10 ns switching time; 2 ns sensing time; 15% write margin; defined as (I W -I C )/I C ; and >40% read-disturb margin, defined as (I C -I R )/I C , in an array comprising 256 rows and 512 columns [29][30][31]. See Table 2 for simulation results.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…During read/write operations, the unbalanced currents flowing over interconnects cause voids which ultimately lead to operation failure by introducing large delay. In [129][130][131], the authors designed a methodology for SRAM EM reliability assessment with considering process variations. The equivalent current distributions over bitlines are calculated with an AFDbased current conversion scheme.…”
Section: Modeling Of Em Impact On Interconnects In Cache Memorymentioning
confidence: 99%
“…The existing works on EM analysis in the signal lines of SRAM [9,10] are based on Blech length formulation, which is too simplistic. They do not consider the impact of various material parameters given in the Korhonen's equation on the EM failure times.…”
Section: Em Modelingmentioning
confidence: 99%
“…However, it has been shown that even signal lines in Static Random Access Memory (SRAM) can have EM failures [9,10]. These works focus on EM analysis for the read operation in SRAM, since the read current is unidirectional and hence self-healing effect is smaller.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation